2009
DOI: 10.1111/j.1751-2980.2009.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

RNAi‐mediated silencing of ezrin gene reverses malignant behavior of human gastric cancer cell line SGC‐7901

Abstract: OBJECTIVE:To investigate the effects of ezrin targeting gene of RNA interference (RNAi) on human gastric cancer cell line SGC-7901 in vitro. METHODS:The highly metastatic human gastric cancer cell line SGC-7901 transfected with a small interfering (siRNA) lentivirus vector was selected for this research study. Expressions of ezrin mRNA and ezrin protein in the SGC-7901 cells were detected using RT-PCR and Western blot. Cell apoptosis was observed using flow cytometry. Transwell invasion and the cell adhesion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In accordance with the tissue sample data indicating the correlation between miR-214 expression and LNM, we found that, compared to the moderately well-differentiated cell line MKN28, miR-214 expression was markedly less in the poorly differentiated cell lines MKN45 and BGC823, and especially the metastatic cell line SGC7901 [14] ( P <0.05).…”
Section: Resultssupporting
confidence: 89%
“…In accordance with the tissue sample data indicating the correlation between miR-214 expression and LNM, we found that, compared to the moderately well-differentiated cell line MKN28, miR-214 expression was markedly less in the poorly differentiated cell lines MKN45 and BGC823, and especially the metastatic cell line SGC7901 [14] ( P <0.05).…”
Section: Resultssupporting
confidence: 89%
“…There is a relationship between high expression of ezrin and metastatic potential of some carcinomas, including medulloblastoma [10], hepatocellular carcinoma [11], lung cancer [12], breast carcinoma [13], pancreatic adenocarcinoma [14], gastric cancer cell [15], and colorectal cancer [16]. We have also demonstrated that ezrin is overexpressed in a malignantly transformed esophageal epithelial cell line compared to an immortalized cell line [17].…”
mentioning
confidence: 63%
“…The inhibition of Ezrin expression clearly inhibits the migration and invasion of the human gastric cancer cell line, SGC-7901, and increases both cell adhesion and sensitivity to camptothecin-induced apoptosis [18]. Overexpression of Ezrin also promoted cell protrusion, microvillus formation, anchorage-independent growth, motility and invasion in the pancreatic cancer cell line, MiaPaCa-2.…”
Section: Discussionmentioning
confidence: 98%